How to Boost Employment and Make Workers Healthier by Application of Novel Economic Instruments - Stenis, Jan (Current Aspects in Business, Economics and Finance Vol. 7, 2023)
Objectives: The Naturally Optimized Revenue Demand in Communities (NORDIC) model was employed to improve the workforce by providing a practical method. Authorities, politicians, and others obtained a tool to modify the labor policy. The launched model considered and promoted the health of the workforce and reduced the costs of non-employment. Methods: The suggested methodology generated artificial shadow costs that were introduced into the public's accounts to provide financial incentives to raise the employment-to-population ratio. One significant factor that only by one digit expressed how effective the labor policy was over time was the associated shadow cost and its impact on the PSBR. Results: This case study showed how the workforce in the Swedish society could be improved by application of the NORDIC model. The findings suggested a promising approach for using economic tools to enhance the well-being of the workforce and raise the employment-to-population ratio. Conclusions: According to the study's findings, the adaptable NORDIC model might be applied to enhance the Swedish workforce and quality of life, especially for seniors. Labor authorities and politicians who want a comprehensive tool to redesign labor policy are potential end users. More research should be focused on developing algorithms for specific segments of the workforce.